Kedudukan Dewan Perwakilan Rakyat (DPR) dalam Penyelesaian Pelanggaran Hak Asasi Manusia yang Berat - Arief Rianto Kurniawan (Badan Strategi Kebijakan Hukum, 2013)
Government has yet to implement the four recommendations once submitted by the DPR to the government, particularly the completion of cases of alleged human rights violations in the past, showed that there was no political will from the government to implement the recommendations . House of Representatives as part of determining whether or not an event for past human rights violations prosecuted merely regarded as a formality. That provision was justified Law No. 26 Year 2000 on Human Rights Court which authorizes Parliament to establish the Ad Hoc Court. However, the investigation is not by Parliament but by an independent agency such as the National Human Rights Commission.